Plasma mycophenolic acid concentration and the clinical outcome after lung transplantation. Issue 12 (4th October 2020) - Yabuki, Hiroshi; Matsuda, Yasushi; Watanabe, Tatsuaki; Eba, Shunsuke; Hoshi, Fumihiko; Hirama, Takashi; Oishi, Hisashi; Sado, Tetsu; Noda, Masafumi; Sakurada, Akira; Kikuchi, Masafumi; Yamaguchi, Hiroaki; et al.
Abstract: Background: The therapeutic drug monitoring of mycophenolic acid (MPA) has been investigated for renal and heart transplantations; however, its usefulness in lung transplantation is unclear. Methods: The MPA area under the plasma concentration–time curve (AUC) was calculated in 59 adult lung transplant recipients. The MPA AUC0‐12 s were compared among the three groups determined by the presence of adverse events (no events, infection, and chronic lung allograft dysfunction [CLAD]). Next, MPA AUC0‐12 thresholds for the adverse events were identified by receiver operating characteristic analysis. Cumulative occurrence rate of the adverse events was compared between two groups (adequate and inadequate groups) according to the thresholds. Results: The MPA AUC0‐12 s in the no event, infection, and CLAD groups were 30.3 ± 6.5, 36.8 ± 10.7, and 20.6 ± 9.6 µg·h/mL, respectively ( P = .0027), while the tacrolimus trough levels were similarly controlled in the groups. The thresholds of MPA AUC0‐12 for the occurrence of infection and CLAD were 40.5 and 22.8 µg·h/mL, respectively. The cumulative occurrence rate of adverse events of adequate group (15.3%) was significantly lower than that of inadequate group (56.0%) ( P = .0050). Conclusions: The MPA AUC0‐12 may affect the occurrence of adverse events in lung transplant recipients.